Identify Students’ Concept Understanding Using Three-Tier Multiple Choice Questions (TTMCs) on Stoichiometry - Rinayu Anintia; Satya Sadhu; Desfi Annisa (Universitas Sebelas Maret, 2017)
The research addressed 1) to develop a three-tier test, 2) to identify students’ concept understanding in stoichiometry. The design of this research is descriptive. Cluster sampling technique with proportional measuring is used to collect 176 selected samples from three different schools. Analyses were conducted to check on content validity, empirical validity, discrimination index, and difficulty index. Findings of the pilot study showed that the content validity is in the range of 0.56 – 1.00 score. The empirical validity value was found to be appropriate and good enough with 28 out of 30 questions are valid with ttable 1.99, reliability is 0.47. Discrimination index was found to be appropriate with 3.57% question in excellent, 42.86% question in good, 42.86% question in fair, and 10.71% question in poor. Difficulty was found to be appropriate with 17.86% questions in convenient and 82.14% question in fair. Identification of students’ concept understanding using three-tier showed that 33.10% of students comprehend the concept correctly, 4.06% students are less understand the concept, 31.53% students are in misconception, 19.50% students did not comprehend the concept, and 11.81% students are guessing.